Increased disease severity induced by some comoviruses in bean genotypes possessing monogenic dominant resistance to bean common mosaic potyvirus - Morales, Francisco José; Castaño, M. (Scientific Societies, 1992)
Three comoviruses isolated from diseased bean plants in Brazil (CV-BZ), Venezuela (CV-VZ), and Honduras (CV-HD) were inoculated to 53 bean genotypes possessing or lacking the dominant alleles of the necrosis (I) gene, which conditions resistance to bean common mosaic virus (BCMV). These comoviruses systemically infected all bean genotypes tested, predominantly inducing mosaic and plant malformation. Symptom expression was considerably enhanced in bean cultivars possessing the dominant I gene, particularly when infected by CV-VZ and CV-HD. The latter comovirus also induced necrotic symptoms in dominant I gene bean cultivars, regardless of the absence or presence of specific recessive genes, which protect the I gene against necrotic BCMV strains. The test comoviruses also induced top necrosis in two bean genotypes, Arbolito Retinto and Honduras 46, which do not possess the dominant alleles of the necrosis gene. The implications of these findings are important considering that most of the improved bean cultivars grown in Latin America, the United States, and Europe possess monogenic dominant resistance to BCMV and that some of the chrysomelid vectors of these comoviruses also are present in temperate countries.